The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/msphere.00649-18
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Clinical Specimens Reveals Extensive Diversity of Legionella pneumophila Strains in Arizona

Abstract: Between 2000 and 2017, a total of 236 Legionella species isolates from Arizona were submitted to the CDC for reference testing. Most of these isolates were recovered from bronchoalveolar lavage specimens. Although the incidence of legionellosis in Arizona is less than the overall U.S. incidence, Arizona submits the largest number of isolates to the CDC for testing compared to those from other states. In addition to a higher proportion of culture confirmation of legionellosis cases in Arizona than in other stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This was based on mapping sequence reads to reference genomes followed by the analysis of either single-nucleotide polymorphism (SNP) or a gene-by-gene approach that reproduces on a larger scale the multi-locus sequence typing (MLST). Whole-genome MLST (wgMLST) has been applied to study the genomic diversity of Lp clinical strains, unrelated to specific epidemic events, and interestingly previously unknown clusters were revealed (Raphael et al, 2019). WGS also showed that a single Lp1 clone was the cause of three outbreaks when SNP, core genome MLST and pangenome approach was used (Timms et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This was based on mapping sequence reads to reference genomes followed by the analysis of either single-nucleotide polymorphism (SNP) or a gene-by-gene approach that reproduces on a larger scale the multi-locus sequence typing (MLST). Whole-genome MLST (wgMLST) has been applied to study the genomic diversity of Lp clinical strains, unrelated to specific epidemic events, and interestingly previously unknown clusters were revealed (Raphael et al, 2019). WGS also showed that a single Lp1 clone was the cause of three outbreaks when SNP, core genome MLST and pangenome approach was used (Timms et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Raw data found on online repositories can be used by different key users with different approaches. We excluded several isolates from our analysis after bad quality results for de novo assemblies based on N50 < 100 000, which generally was associated to discordant genome length and /or high N bases numbers, nevertheless they were presented by studies considering these isolates of reliable quality after using another de novo alignment protocol (Supplementary Table S1) [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Quality scores of each method for each isolate are found in the Supplementary Table S1. N-50 was superior to 100,000, Q-score at least 30 (32)(33)(34)(35)(36)(37)(38) and average de novo covering was superior to 40 (46 -203) [15,28].…”
Section: Bioinformatic Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, issues remain for highly represented STs like ST1 [8,12,15,16]. Indeed, ST1 is known to be both genetically highly conserved and ubiquitous, but its population structure remains poorly described [19]. We carried out a mini review of L. pneumophila genomic studies conducted since 2015 in order to explore the methods and clustering thresholds used to investigate both outbreaks and long-term surveillances of L. pneumophila to identify which to apply to our specific question (Table 1).…”
Section: Casementioning
confidence: 99%